Idiopathic External Cervical Resorption of the Impacted Second Premolar: A Case Report - Eglė Zasčiurinskienė; Liveta Rastokaitė; Pedram Hosseinzadehfard; Greta Lodienė (Applied Sciences, 2023)
The tooth impaction of the lower second premolars is an occasional condition but is still seen in clinical practice with a prevalence of 0.6–2.6%. The present case report describes a rare condition of the lower second premolar impaction. An 11-year-old female patient presented with the anteroposterior dental discrepancy, midline shift, and occlusal cant. Intraoral examination revealed the absence of the lower right second premolar with no space available for the eruption. X-ray examination revealed the impaction of tooth #45 in a vertical position, tilting of the adjacent teeth, and two-thirds root length development. The orthodontic treatment plan included space opening using a fixed appliance with a coil spring. The natural eruption of the tooth was expected according to dental age and root development. When the space was opened, no change in the position of tooth #45 was observed. Surgical exposure and active traction were performed. However, the intrusion and tilting of adjacent teeth were observed during the next appointments with no vertical change of tooth #45. Ankylosis was suspected as no tooth movement was recorded. The surgical luxation and osteotomy of the coronal alveolar bone of the impacted tooth were planned for the imminent forced eruption, which was expected due to the young age of the patient. Consequently, the crown of tooth #45 emerged and the bracket was placed. Further traction was planned to use a micro-screw. Following the traction, no vertical displacement of the tooth was observed in the subsequent appointments. Radiographic examination revealed radiolucency in the coronal third of the root. The patient was referred to the endodontist, and CBCT revealed external cervical root resorption in the late reparative stage. ECR in an impacted tooth, mimicking the manifestation of tooth ankylosis, can cause orthodontic treatment failure.